E-commerce Extends to M-commerce - Vijaya kumar, Jacqueline Gigi (Indian Journal of Marketing, 2005)
"A dream cherished since the advent of mobile phone services in the country, came truly today with the Railway minister, Lalu Prasad, inaugurating the launch of reservation of rail tickets through mobile phone at a function in New Delhi". This news has made every Indian to sit up and marvel at the magic world of mobile, where mobile equipments are used for services much more than simply making phone calls. In the year 2000, Mr.Gedaliah Gurfein, the vice president of an Israeli firm TeleVend stood in front of a soda machine with 'No cash needed' emblazoned on its front. He whipped out his cellular phone and dialed the number printed on the front of the machine. An automated voice welcomed him to the 'TeleDrink' system said his purchase would be automatically billed to his cell phone and asked him to press 1 for cola, 2 for a diet cola,3 for an orange drink or 4 for a soda water. He pressed 1 and a cold can of cola popped out. Mr. Gurfein was on stage at Demo 2000, a two day conference known as a launch pad for new tech products, ideas and companies. He envisioned a future where users can do everything from feeding their parking meters, to ordering a pizza, to pumping gas just by dialing the appropriate phone numbers from their mobile phones.